Impact of Land use on soil quality: Insights from the forest-savannah transition zone of Ghana - Johnny Kofi Awoonor; Emmanuel Amoakwah; Mohammed Moro Buri; Bright Fafali Dogbey; Jackson Kwame Gyamfi (Heliyon)
Land use changes have a profound impact on soil fertility and agricultural production systems in the Forest-Savannah Transition Zone (FSTZ) of Ghana. Soil erosion and shortened fallow periods exacerbate soil fertility loss, further degrading soil quality. This study aimed to: (i) quantify soil quality indices, and (ii) assess soil fertility status across different land use types (Forest, Savannah Woodland, Grassland, Fallow, and Cropland) at two soil depths (0–20 cm and 20–50 cm). The 0–20 cm depth represents the plough layer, while 20–50 cm captures nutrient leaching in the Nkoranza districts. Using principal component analysis (PCA), we reduced the number of indicators from 29 to 9, capturing 94.42 % and 94.81 % of variability in the topsoil and subsoil, respectively. Key indicators included sand, silt, gravel content (Gco), electrical conductivity (EC), available phosphorus (Av. P), exchangeable potassium (Ex. K), microbial biomass carbon (MBC), nitrogen (MBN), and phosphorus (MBP). Results indicated that subsoil had a higher Soil Quality Index (SQI) (0.60) than topsoil (0.57), reflecting surface soil degradation. Forests recorded the highest SQI (0.67), while Croplands had the lowest (0.54). Communality estimates revealed that sand, silt, Gco, EC, Av. K, Av. P, MBC, and MBN were the most influential indicators, with the highest weights (0.11) at both depths. The SQI was positively correlated with maize yield (R2 = 0.61, p < 0.05), with available K (0.033) and P (0.010) being critical yield indicators. Croplands (0.54) and Fallow lands (0.53) showed the highest nutrient depletion due to inappropriate land use by smallholders. This research provides the foundation for policymakers at the local, regional, and national levels to develop strategies for improving soil management and increasing maize production in the FSTZ of Ghana.